Semiokimia dan volatil lain pada Cheilomenes sexmaculata (Fabricius) (Coleoptera: Coccinellidae) yang memangsa Aphis gossypii Glover (Hemiptera: Aphididae) pada tanaman cabai: Semiochemicals and other volatiles on Cheilomenes sexmaculata (Fabricius) (Coleoptera: Coccinellidae) that prey on Aphis gossypii Glover (Hemiptera: Aphididae) on chili plants - Efendi, Siska; Dadang, Dadang; Winasa, I Wayan; Nurmansyah, Ali (Perhimpunan Entomologi Indonesia, 2024)
Cheilomenes sexmaculata (Fabricius) is a potential natural enemy of aphids. Various aspects of the ecology and biology of this predator have been studied; however, there is still limited information on its physiology, particularly regarding pheromones and other semivolatiles. Naturally, intraspecific and interspecific interactions of C. sexmaculata involve a variety of semiochemicals. The information on the semiochemicals of C. sexmaculata, particularly its sex pheromones, footprints, defense mechanisms, aggregation, and other semivolatile characteristics, is still limited in Indonesia. This research was aimed to identify the semiochemical produced by the female of C. sexmaculata. The volatile compounds emitted by C. sexmaculata were captured using the headspace solid-phase micro extraction (SPME) method. The identification and quantification of each volatile compound were analyzed using gas chromatography-mass spectrometry (GC-MS). A total of 47 volatile compounds was identified among the semivolatiles. The identified volatiles comprise 47 compounds, mainly from the hydrocarbon compunds. Methyl isovalerate was the compound with the highest proportion, namely 31.43%. Several compounds identified were known to be components of the C. sexmaculata pheromone, namely methyl isovalerate, limonene, undecane, dodecane, and eicosane. These compounds were reported as components of sex pheromones, aggregation, and alarm. The limonene identified in this experiment was also previously reported in several Coccinelliade as a component of aggregation pheromone.